Gender Relations in Urban-Popular Qur'anic Exegesis: Repackaging Patriarchal Authority in Ahmad Sarwat's Tafsir Al-Mahfuzh - Seri Asmita Harahap; Ida Kurnia Shofa; Khoirun Nidhom; Bensar A. Muin (Universitas Muhammadiyah Surakarta, 2026)
Purpose - Studies on gender in Indonesian Qur'anic exegesis have largely focused on progressive-hermeneutical interpretations, while fiqh-oriented tafsir circulating in urban digital spaces remains understudied. This study aims to examine the construction of gender relations in Ahmad Sarwat's Tafsir Al-Mahfuzh, particularly in his interpretation of Q.S. An-Nisa' verses 1, 11, and 34, and to identify its ideological position within contemporary Indonesian exegetical discourse. Design/methods/approach - This research employs a qualitative library research design. Data were collected through systematic close reading of Tafsir Al-Mahfuzh and analyzed using content analysis and textual interpretation. The analysis focuses on three dimensions of gender relations: ontological (human creation), socio-economic (inheritance distribution), and structural (qawwamah and family leadership). Findings - The study identifies a paradigm of Traditionalist Complementary Hierarchy. Sarwat affirms ontological and spiritual equality between men and women but maintains asymmetrical socio-juridical authority structures. Classical patriarchal concepts are reformulated through modern urban-managerial language without altering their underlying epistemological foundations. While the interpretation promotes ethical moderation by restricting physical violence, it rejects substantive restructuring of domestic power relations and continues to privilege male leadership within the family. Research implications/limitations - The study is limited to textual analysis of three selected verses in a single exegetical work and does not investigate audience reception or the influence of digital dissemination on interpretation. Originality/value - This research proposes the concept of Urban-Popular Exegesis, a typology characterized by innovation in medium and presentation while maintaining conservative legal substance. The findings demonstrate that digital religious platforms may reinforce refined forms of patriarchy rather than necessarily promoting liberalized interpretations of gender in Islam.